1989
DOI: 10.1096/fasebj.3.8.2785942
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep deprivation on human immune functions

Abstract: The effect of 40 h of wakefulness on a variety of immunological parameters in the peripheral blood from 10 normal male subjects was studied. Sleep deprivation led to enhanced nocturnal plasma interleukin 1-like and interleukin 2-like activities. The rise in nocturnal response of lymphocytes to pokeweed mitogen stimulation during a normal 24 h sleep-wake cycle was delayed by sleep deprivation, but the response to the phytohemagglutinin mitogen was unaffected. With resumed nocturnal sleep, there was a prolonged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
105
1
2

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(115 citation statements)
references
References 18 publications
7
105
1
2
Order By: Relevance
“…Interestingly, we found that NK activity increased following two nights, but not one night, without sleep. This outcome is consistent with the results of Moldofsky et al (9), who reported that 40 h of sleep loss had no clear effects on NK activity, but in a subsequent study found that 64 h without sleep elevated NK activity during the early evening hours (10). The lag in NK activity in response to sleep loss may reflect the transient decreases in NK cell counts we observed after the first night without sleep.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, we found that NK activity increased following two nights, but not one night, without sleep. This outcome is consistent with the results of Moldofsky et al (9), who reported that 40 h of sleep loss had no clear effects on NK activity, but in a subsequent study found that 64 h without sleep elevated NK activity during the early evening hours (10). The lag in NK activity in response to sleep loss may reflect the transient decreases in NK cell counts we observed after the first night without sleep.…”
Section: Discussionsupporting
confidence: 92%
“…Palmblad et al (7) found increased IFN production during and after 77 h of sleep loss. Moldofsky et al (9) found that 40 h of sleep deprivation enhanced IL-1-like and IL-2-like activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that NK cells defend against tumor cell growth and viral infections in human cellular immune systems, and that NK cell functions are variously influenced by workload [15][16][17] , mental health 20-22, 24, 25) , and life style [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] . As for life style, it was reported that reduction of NK cell functions was associated with cigarette smoking [34][35][36][37][38] , shortened daily sleep 17) , disturbed sleep [39][40][41] , circadian rhythm (high activity in the morning and low activity at night) [42][43][44][45] , and excessive physical exercise 46,47) .…”
Section: Discussionmentioning
confidence: 99%
“…As for life style, it was reported that reduction of NK cell functions was associated with cigarette smoking [34][35][36][37][38] , shortened daily sleep 17) , disturbed sleep [39][40][41] , circadian rhythm (high activity in the morning and low activity at night) [42][43][44][45] , and excessive physical exercise 46,47) . Conversely, healthy life styles (i.e., good sleep, adequate physical exercise, and so on) were associated with increases of NK cell functions [48][49][50] .…”
Section: Discussionmentioning
confidence: 99%